2000
DOI: 10.1021/jp000272o
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption and Decomposition of C2H4 on Ru(001):  A Combined TPR and Work Function Change Study

Abstract: Work function change (∆Φ) measurements during adsorption and surface heating in a ∆Φ-temperature programmed reaction (TPR) mode combined with TPD are demonstrated to provide new information on the interaction and chemistry of ethylene on Ru(001). Rearrangement of second layer ethylene molecules has been observed between 82 and 120 K. This is a competing process with molecular desorption, interpreted as a result of migration of second layer molecules toward the surface. Our results are consistent with and suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…We assumed a linear relationship between the work function change and surface coverage, which at the least can be considered an approximation to trends in reaction behavior. This method has already been successfully applied by Livneh and Asscher [28], who studied the decomposition of ethene on Ru(001) using work function measurements and found that the work function change during decomposition was linear at lower coverage but reached saturation at high coverage.…”
Section: Hydrogenation Of Butadiene On Pdsn/pd(111) Surface Alloysmentioning
confidence: 99%
“…We assumed a linear relationship between the work function change and surface coverage, which at the least can be considered an approximation to trends in reaction behavior. This method has already been successfully applied by Livneh and Asscher [28], who studied the decomposition of ethene on Ru(001) using work function measurements and found that the work function change during decomposition was linear at lower coverage but reached saturation at high coverage.…”
Section: Hydrogenation Of Butadiene On Pdsn/pd(111) Surface Alloysmentioning
confidence: 99%
“…As noted above, in prior EELS‐based characterization of Ru(0 0 0 1) samples dosed in a high‐pressure cell with T Ru ≈400 K and carbon coverages ≥0.6 ML of carbon, Goodman and co‐workers reported the presence of CCH 2 (ads) (vinyledine) by observation of its C=C stretching mode at ≈1160 cm −1 and the CH 2 scissor mode of CCH 2 (ads) at 1400 cm −1 . Prior studies have concluded that CCH 2 assumes a configuration on Ru(0 0 0 1) in which the C=C bond is orthogonal to the plane of the surface . In this configuration the two CH stretches would be expected to couple, giving symmetric and asymmetric stretches, with the transition dipole of the symmetric stretch orthogonal to the surface and that of the asymmetric stretch parallel.…”
Section: Resultsmentioning
confidence: 93%
“… Dissociation pathway of C 2 H 4 dosed on Ru(0 0 0 1), predicted by EELS, RAIRS, and temperature‐programmed oxidation (TPO) measurements . The dissociation steps from CCH 3 to CCH remain unclear; CCH 2 is expected to be an intermediate, but has not been previously reported.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The experiments described here were conducted in a previously described 32 Ultra High Vacuum (UHV) system at a base pressure of ∼2 × 10 −10 Torr. A 0.8 × 0.8 cm 2 Ru(0001) single crystal is daily cleaned via a 10 min sputter using high energy ions (Ar + at 700 eV) with subsequent flash annealing to 1600 K and then stay at 1400 K for two more minutes.…”
Section: Experimental Set Upmentioning
confidence: 99%